Alcohol-associated hepatitis trends before and following the onset of the COVID-19 pandemic across two distinct cohorts in the United States and Hong Kong - Zeyuan Yang; Vicki Wing-Ki Hui; Terry Cheuk-Fung Yip; Mandy Sze-Man Lai; Jimmy Che-To Lai; Vincent Wai-Sun Wong; Ramsey Cheung; Grace Lai-Hung Wong; Robert J. Wong (JHEP Reports)
Background & Aims: Alcohol-associated liver disease (ALD) burden has been rising globally, fueled by increases in high-risk alcohol use following the coronavirus disease 2019 (COVID-19) pandemic. We evaluated trends in annual incidence of alcohol-associated hepatitis (AH) before and following the onset of the COVID-19 pandemic across two geographically distinct populations in the USA and Hong Kong. Methods: Using US national Veterans Affairs (VA) data and Hong Kong territory-wide data, trends in annual incidence of AH were evaluated from 2000 to 2023. AH was identified using a combination of International Classification of Diseases (ICD)-9/10 diagnostic codes, laboratory data, and available alcohol use data. Results: Among the VA data, annual incidence of AH rose steadily from 39.4 to 53.7 per 100,000 persons (2010–2020), then declined to 36.2 per 100,000 persons in 2023. Annual AH incidence was substantially lower in Hong Kong, but demonstrated similar trends, peaking at 0.28 per 100,000 persons during the first year of the pandemic. Among both cohorts, incidence of AH was significantly higher in men vs. women, but particularly for the VA cohort, the increase in AH incidence was more rapid in women. Among both cohorts, the highest incidence of AH in 2023 was among the 40–49-year age group (VA: 72.7 per 100,000 persons; Hong Kong: 1.89 per 100,000 persons). Conclusions: We provide a comprehensive analysis of epidemiological trends in AH incidence across two distinct populations, highlighting the need for continued awareness of targeted interventions to curb unhealthy alcohol use and its complications. Impact and implications:: Alcohol-associated hepatitis (AH) is a severe complication of high-risk alcohol use associated with significant morbidity and mortality. Increasing alcohol use fueled by the COVID-19 pandemic has led to parallel increases in alcohol-related comorbidities. The current study provides a comprehensive analysis of trends in the incidence of AH across two distinct world regions before and following the onset of the COVID-19 pandemic. Better identification of epidemiological trends in AH incidence as well as highlighting populations most affected can help target public health resources and health system interventions to address the dangers of high-risk alcohol use more effectively.